2012
DOI: 10.1038/nm.2656
|View full text |Cite
|
Sign up to set email alerts
|

High abundance of plasma cells secreting transglutaminase 2–specific IgA autoantibodies with limited somatic hypermutation in celiac disease intestinal lesions

Abstract: Celiac disease (CD) is an immune mediated disorder in which mucosal autoantibodies to the enzyme transglutaminase 2 (TG2)1 are generated in response to the exogenous antigen gluten2 in individuals who are HLA-DQ2 or HLA-DQ83. We assessed in a comprehensive and non-biased manner the IgA anti-TG2 response by expression cloning of the antibody repertoire on ex vivo isolated intestinal antibody-secreting cells (ASCs). We found that TG2-specific plasma cells are hugely expanded in patients with active CD, represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
305
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(331 citation statements)
references
References 45 publications
22
305
1
3
Order By: Relevance
“…Also, although plasma cells secreting anti-gluten and autoantibodies are present in celiac intestinal lesions (17-19), we did not detect a similar increase in intestinal-homing B cells (not shown). This is consistent with reports indicating that tissue transglutaminasespecific B cells were undetectable in the peripheral blood of celiac patients (19,20). In summary, dietary gluten induces the activation and concomitant peripheral blood presence of CD4 + and CD8 + αβ T cells and γδ T cells with gut-homing potential in celiac patients who have been on a gluten-free diet ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Also, although plasma cells secreting anti-gluten and autoantibodies are present in celiac intestinal lesions (17-19), we did not detect a similar increase in intestinal-homing B cells (not shown). This is consistent with reports indicating that tissue transglutaminasespecific B cells were undetectable in the peripheral blood of celiac patients (19,20). In summary, dietary gluten induces the activation and concomitant peripheral blood presence of CD4 + and CD8 + αβ T cells and γδ T cells with gut-homing potential in celiac patients who have been on a gluten-free diet ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…That all 19 mAbs generated were genetically unrelated and used multiple V genes in each patient shows that there was not preferred V-gene use like those seen in autoantibodies against TG2 (7). The fact that the autoantibodies were polyclonal excludes a single forbidden clonotype of pathogenic autoantibodies in each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one notion for the origin of pathogenic autoantibodies is the propensity of certain V genes or alleles or preferred combinations of H and L chains to give rise to high-affinity autoantibodies against self-antigens (6). An elegant study showed that authentic human monoclonal autoantibodies (mAbs) against transglutinaminase 2 (TG2) in celiac disease used preferred V genes (7). There were few somatic mutations in the mAbs so that germ-line V genes could produce high-affinity autoantibodies against TG2, but whether the autoantibodies against TG2 are pathogenic for celiac disease is unclear (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The panel of TG2-specific mAbs described above was generated from small intestinal biopsies of celiac disease patients (23). Based on competitive ELISA experiments, we recently showed that 49 of 57 mAbs could be placed into one of four distinct epitope groups (epitope 1-4, targeted by 30, 6, 11, and 2 mAbs, respectively), which correlated with mAb VH-segment use.…”
Section: Disulfide Bond Formation In Itg2 Prevents the Stabilizing Efmentioning
confidence: 99%